A wavy flow channel system for membrane fouling control in oil/water emulsion filtration - Barambu, N.U. (Elsevier Ltd, 2021)
The membrane-based process is attractive for the treatment of oil/water emulsion because of its effectiveness in handling micron size oil droplets. However, membrane fouling due to the strong oil droplets/membrane surface interplay remains its major challenge that limits its widespread application. This study reports a new approach for membrane fouling control via a wavy flow channel to enhance the effective area and improve the local mixing. The hydraulic performance of a membrane was used to assess the effectiveness of the system against the traditional straight flow for oil/water emulsion treatment. Results show that the wavy flow channel offers two main advantages: increasing the membrane effective surface area and facilitate swirling flows that effectively promote fouling control. The wavy flow channel showed up to ~58 higher permeability (of 219.1 Â± 5.8 L.mâ2.hrâ1.barâ1) than the reference, in which 18 was due to the enhanced flow property. The energy loss due to additional shear stress and longer flow path only contributed to a 7 additional pressure drop. The energy to overcome the pressure drop was insignificant to the specific energy consumption, which showed that the wavy membrane offered 21 energy saving (0.015 vs 0.019 kWh/m3). This study opens an option in improving membrane filtration performances via a simple module-scale modification suitable for fouling prone pressure-driven membrane systems. Â© 2021 Elsevier Ltd